Health Risks Associated With Excessive Exposure to Solar Ultraviolet Radiation Among Outdoor Workers in South Africa: An Overview - Wright, Caradee Y.; Norval, Mary (Frontiers in Public Health, 2021)
Exposure of outdoor workers to high levels of solar ultraviolet radiation (UVR) poses significant, well-known health risks including skin cancer and eye diseases. In South Africa, little is known about how many workers are potentially overexposed to solar UVR and what the associated impacts on their health might be. Here, the geography and solar UVR environment in South Africa are considered, as well as the different outdoor occupational groups likely to be affected by excessive solar UVR exposure. Sunburn, pterygium, cataract, keratinocyte cancers and melanoma are discussed in the context of outdoor workers. Few studies in South Africa have considered these health issues and the most effective ways to reduce solar UVR exposure for those working outside. Several countries have developed policies and guidelines to support sun safety in the workplace which include training and education, in addition to the provision of personal protective equipment and managerial support. Several gaps in occupational sun protection and workplace sun safety for South Africa are identified. Legislation needs to recognise solar UVR exposure as an occupational health hazard, with sun safety guidelines and training provided for employers and employees.